Enhancing the role of Islamic ethics in facing the challenges of globalization and post modernity: looking for a holistic definition - Awang Abd. Rahman @ Jusoh, Amilah (s.n, 2014)
This research looks for a holistic definition of Islamic ethics by considering the effect of the challenge of globalization and post modernism. It is very fundamental and needs to be discussed in a new approach. This is especially important because the available picture is agreed by Muslim ethicist to be fragmented and lack of composite approach as well as analytical approach.